Evaluasi Penggunaan Bahu Jalan pada Perkerasan Kaku di Kota Makassar - Winarno Arifin; Rani Bastari Alkam; Rachmatan Rachmatan (Jurnal Inovasi dan Pelayanan Publik Makassar, 2019)
In Makassar City, some residents or individuals utilize the roadsides by transitioning its functions for personal or business purposes by altering its physical form. This study aims to evaluate the use of the roadsides in rigid pavement in Makassar, namely by identifying points on the section of rigid Pavement with the misuse of the roadsides based on Indonesian rules of the road main space. The target to be achieved is to provide recommendations on measures to organize the roadsides uses for the development of the physical sector and infrastructure. This research was conducted with a research method based on observation. The results showed that misuse of the roadside occurred in 77.2% of the total of the rigid pavement sections where there was a shift in the function of the roadside, 49% for private needs and 51% for commercial purposes. Besides, there was a physical change, elevated the roadsides with slope exceeding the normal slope (175 cases), and drainage closure (92 cases) and both (17 cases). For this reason, it is necessary to prevent and deal with roadside’s misuses by making a social-based regional regulation referring to the laws and regulations of the central government by actively involving the society in its implementation.